2007
DOI: 10.1002/jcp.21205
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 upregulates EGF‐stimulated signaling in mitogenic pathways involving Akt and ERK in hepatocytes

Abstract: Prostaglandins (PGs) such as PGE2 enhance proliferation in many cells, apparently through several distinct mechanisms, including transactivation of the epidermal growth factor (EGF) receptor (EGFR) as well as EGFR-independent pathways. In this study we found that in primary cultures of rat hepatocytes PGE2 did not induce phosphorylation of the EGFR, and the EGFR tyrosine kinase blockers gefitinib and AG1478 did not affect PGE2-stimulated phosphorylation of ERK1/2. In contrast, PGE2 elicited EGFR phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 77 publications
4
41
0
1
Order By: Relevance
“…This is in agreement with our previous observation that cAMP does not mediate the proliferative effects of prostaglandins in the hepatocytes (Refsnes et al, 1995). Furthermore, although EP4 receptors have been found to stimulate cyclin D1 expression and phosphorylation of EGF receptor and extracellular signal-regulated kinase in murine hepatocytes (Kataoka et al, 2005), prostaglandins do not transactivate the EGF receptor in rat hepatocytes (Nilssen et al, 2004) but act to enhance subsequent stimulation of extracellular signal-regulated kinase and Akt by EGF (Dajani et al, 2007). In addition, we found no additive effects between sulprostone and misoprostol on DNA synthesis, suggesting lack of involvement of EP4 receptors.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with our previous observation that cAMP does not mediate the proliferative effects of prostaglandins in the hepatocytes (Refsnes et al, 1995). Furthermore, although EP4 receptors have been found to stimulate cyclin D1 expression and phosphorylation of EGF receptor and extracellular signal-regulated kinase in murine hepatocytes (Kataoka et al, 2005), prostaglandins do not transactivate the EGF receptor in rat hepatocytes (Nilssen et al, 2004) but act to enhance subsequent stimulation of extracellular signal-regulated kinase and Akt by EGF (Dajani et al, 2007). In addition, we found no additive effects between sulprostone and misoprostol on DNA synthesis, suggesting lack of involvement of EP4 receptors.…”
Section: Discussionsupporting
confidence: 93%
“…EGFR is a multifunctional tyrosine kinase receptor with the ability to active multiple effectors and downstream signaling pathways (48,49). In the current study, we observed that EP2 agonist-mediated transactivation of EGFR resulted in the activation of the downstream signaling effectors: ERK1/2, Akt, and STAT3.…”
Section: Discussionmentioning
confidence: 54%
“…ERK1/2 and Akt are known to be activated in cultured cells by PGE 2 (20,48,50) and to play important roles in cell proliferation and skin tumor formation (33,36). Several reports indicated that PGE 2 -stimulated ERK1/2 and Akt activation were mediated by both activated EGFR and activated PKA (20,48,51) and that both effectors contributed to keratinocyte replication and survival (33,35). However, in the present studies, Akt activation was suppressed by EGFR inhibition but not by inhibition of PKA (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…From a more generalized view, prostaglandins may act to potentiate the action of growth factor signals. In an analogous model, PGE 2 may augment the action of platelet-derived growth factor; PGE 2 has low mitotic activity on its own but augments the platelet-derived growth factor signal to increase cell growth (11). Thus, some prostaglandins may act to modulate trophic signals, providing another level of regulation for key signaling pathways.…”
Section: Discussionmentioning
confidence: 99%